Mechanical engineers' handbook : (Wiley, 2006)
Manufacturing and Management is comprised of two major parts covering manufacturing and management. The centerpiece of part one, "the handbook within the handbook," covers manufacturing topics related to production, metal working, statistical quality control, and computer-integrated manufacturing. Topics new to the handbook include physical vapor deposition, environmentally conscious manufacturing, and dealing with process technology in the context of design, tooling, manufacturing, and quality engineering.